(untitled) (Research, Society and Development, 2021)
Objective: To identify the prevalence and risk factors for the development of Burnout syndrome (BS) in medical professors, as well as their reflexes on quality of life. Methods: This is a systematic review of the prevalence of BS in medical professors. The present study was based on the methodological principles for searching for articles in the electronic databases: LILACS, PubMed, SciELO and the Google Scholar platform, with a 10-year time cut (2011-2021). The following descriptors were used to track articles indexed in the databases: “Burnout, Professional” and “Faculty, Medical”. Results: Were included 15 articles, in Portuguese, English and Spanish. The articles address the prevalence, consequences, risk factors and protective factors for BS in medical professors. Conclusion: BS, in general, has a high prevalence among medical professors. Studies show that medical school teachers are in a relatively vulnerable condition for mental exhaustion, as they are exposed to several risk factors for the development of BS. Thus, they are related to increased emotional exhaustion and depersonalization, resulting in less professional achievement. In addition, it was possible to establish a negative correlation between Burnout and the quality of life of medical professors. However, greater methodological standardization and more studies in the area are necessary in order to better establish the impact of this problem on the teaching-learning process and / or the definition of strategies for preventing teachers’ mental illness.